Biomarkers of Targeted Therapy and Immuno-Oncology in Cancers Metastatic to the Breast. Issue 9 (October 2020) - Vranic, Semir; Senarathne, Wijendra; Stafford, Phillip; Poorman, Kelsey; Pockaj, Barbara A.; Gatalica, Zoran
Abstract : The breast is a rare site for metastases, and their molecular characteristics have not been studied yet. Intrinsic molecular genetics, cancer characteristics, and breast tissue immune responses in diverse metastases to the breast have not been previously studied. We identified 64 patients with cancers metastatic to the breast: 51 carcinomas and 13 melanomas. Programmed death ligand 1 (PD-L1), steroid receptors, and HER2/neu expressions were evaluated using immunohistochemistry. Gene sequencing, copy number alterations, microsatellite instability, and tumor mutational burden were performed using next-generation sequencing platforms. The 3 most common primary sites for metastatic carcinomas were lung (37%), ovary (29%), and fallopian tubes/peritoneum (14%). TP53 mutations were commonly (50%) observed among the carcinoma cases, while other mutations were characteristic for the primary cancers ( VHL in renal, BRCA1 in the fallopian tube, and BRAF in melanomas). High tumor mutational burden was detected in 5/14 carcinomas and 3/7 melanomas. Tumor cell PD-L1 expression was detected in 6 carcinomas, but not in any of the melanomas, whereas immune cells' expression of PD-L1 was seen in 17 carcinomas and 6 melanomas. Estrogen receptor status was positive in 13/49 carcinomas including 12 adenocarcinomas originating from the ovary and fallopian tube or peritoneum and 1 duodenal neuroendocrine carcinoma. No carcinoma was HER2/neu positive. Intrinsic genetic characteristics of the metastases to the breast followed the pattern commonly seen in primary tumors. Biomarkers of potential benefit to immune checkpoint inhibition therapy were limited to PD-L1-positive non–small cell lung cancer. No common characteristics of the heterogeneous group of tumor metastases to this organ were identified. Abstract : Supplemental Digital Content is available in the text.